Restoring Blood Pressure in Hypertensive Mice Fails to Fully Reverse Vascular Stiffness - Steppan, Jochen; Jandu, Sandeep; Savage, William; Wang, Huilei; Kang, Sara; Narayanan, Roshini; Nyhan, Daniel; Santhanam, Lakshmi (Frontiers in Physiology, 2020)
Background: Hypertension is a well-established driver of vascular remodeling and stiffening. The goal of this study was to evaluate whether restoring normal blood pressure (BP) fully restores vascular stiffness toward that of normotensive controls. Methods: C57Bl6/J male mice received angiotensin II (angII; 1 µg/kg/min) via infusion pump for 8 weeks (hypertension group: HH), angII for 4 weeks (hypertension group: H4), angII for 4 weeks followed by 4 weeks of recovery (reversal group: HN), or sham treatment (normotensive group: NN). BP, heart rate, and pulse wave velocity (PWV) were measured longitudinally. At the end of the study period, aortas were harvested for testing of vasoreactivity, passive mechanical properties, and vessel structure. Results: The HH group exhibited a sustained increase in BP and PWV over the 8-week period (p<0.01). In the HN group, BP and PWV increased during the 4-week angII infusion, and, though BP was restored during the 4-week recovery, PWV exhibited only partial restoration (p<0.05). Heart rate was similar in all cohorts. Compared to NN controls, both HH and HN groups had significantly increased wall thickness (p<0.05 HH vs. NN, p<0.01 HN vs. NN ), mucosal extracellular matrix accumulation (p<0.0001 HH vs. NN, p<0.05 HN vs. NN), and intralamellar distance (p<0.001 HH vs. NN, p<0.01 HN vs. NN). Both intact and decellularized vessels were noted to have significantly higher passive stiffness in the HH and H4 cohorts than in NN controls (p<0.0001). However, in the HN cohort, intact vessels were only modestly stiffer than those of NN controls, and decellularized HN vessels were identical to those from the NN controls. Compared to NN controls, the HH and HN cohorts exhibited significantly diminished phenylephrine-induced contraction (p<0.000) and endothelium-dependent vasodilation (p<0.05). Conclusion: Hypertension causes a significant increase in in vivo aortic stiffness that is only partially reversible after BP normalization. Although hypertension does lead to matrix stiffening, restoration of BP restores matrix mechanics to levels similar to those of normotensive controls. Nevertheless, endothelial and vascular smooth muscle cell dysfunction persist after restoration of normotension. This dysfunction is, in part, responsible for augmented PWV after restoration of BP.